Batik patterns in the South of Thailand / Worasuda Khwansuwan - Khwansuwan, Worasuda (Faculty of Art and Design, 2021)
"Batik" or "Pateh" is an important cloth in the south of Thailand. Its unique features such as pattern, colour, and production process make Batik different from other cloth in the other part of Thailand. Traditionally, Batik was originated in Indonesia and India where people used paraffin wax as a dye-resist paint. It was also reported that other Asian countries such as Japan and India made Batik fabric in their country. In Thailand, local people in the south made their clothes from Batik fabric and wore them in daily life or during special social events. They designed pattern and applied wax-resist dyeing by hand or blocks on the fabric to create colourful and creative designs. Batik is a cultural identity of the south of Thailand. The study found that the process of creating pattern and colour for Batik was used a long time ago. In the past, artisans primarily employed wooden molds or blocks and wax to create patterns. Through the accumulation of knowledge and experience over time, the development of metal blocks makes Batik's patterns more delicate and vivid. In addition, the research aimed to study about Batik pattern in the southern provinces of Thailand.It can be said that Batik is a uniquely beautiful fabric that should be collected as a national heritage and for the future study of this fabric. The study of Batik pattern in the south revealed that former patterns simply used basic geometric shapes such as lines, squares, and circles. Then, these patterns have been developed by integrating rhythms and spaces to create more distinctive and delicate designs. Moreover, the patterns of Batik in the south were inspired by nature, religious beliefs, and ways of life. Warm tone colours such as red, brown, yellow and cool tone colours such as blue and green were employed. It was also found that the materials used in the past were primarily from plants and nature. Nowadays, artificial colors are also used because they allow vivid and durable effects.